Identifikasi dan Kuantifikasi Kadar Protein pada Putih Telur Bebek (Anas domesticus) - Yulistia, Siska; Parbuntari, Hesty (UNIVERSITAS SERAMBI MEKKAH, 2024)
Proteins found in animal foods such as eggs are said to be perfect proteins. One example of high protein is duck eggs. In this practicum, qualitative analysis of protein was carried out using the biuret color reagent test, while quantitative analysis was carried out using UV-Vis spectrophotometry. The results of the experiment showed that the protein content of the duck egg white was positive for protein, which was indicated by the presence of a purple color. In qualitative analysis with UV-Vis spectrophotometry method with variations in the concentration of standard solutions, namely 0.2, 0.4, 0.6, 0.8, 1 mg/mL. The maximum wavelength obtained at a concentration of 0.6 mg/ml is 815 nm.